2001
DOI: 10.1359/jbmr.2001.16.3.572
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Hip Fracture in Asian Men and Women: The Asian Osteoporosis Study

Abstract: The objectives of the Asian Osteoporosis Study (AOS) were to determine risk factors for hip fracture in men and women in four Asian countries, that is, Singapore, Malaysia, Thailand, and the Philippines. A total of 451 men and 725 women (aged 50 years and over) with hip fractures were compared with an equal number of community controls. A standardized questionnaire was administered by interview. The following relative risks (RRs) were found in women and men by multiple logistic regression: dietary calcium inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
78
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 29 publications
(34 reference statements)
6
78
1
Order By: Relevance
“…The mechanisms by which urbanization may impact hip fracture rates are not known, but may include decreased physical activity, an increase in hard surfaces, calcium and vitamin D deficiencies, (78) or other lifestyle factors. (79,80) Increased urbanization could also reflect an associated increase in prosperity and access to medical care, which could, theoretically, increase survival of the frailest elderly, as was recently proposed as a possible contributor to the increase in fracture rates among older Korean women.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which urbanization may impact hip fracture rates are not known, but may include decreased physical activity, an increase in hard surfaces, calcium and vitamin D deficiencies, (78) or other lifestyle factors. (79,80) Increased urbanization could also reflect an associated increase in prosperity and access to medical care, which could, theoretically, increase survival of the frailest elderly, as was recently proposed as a possible contributor to the increase in fracture rates among older Korean women.…”
Section: Discussionmentioning
confidence: 99%
“…Physical inactivity has long been identified as a risk factor for osteoporosis [82][83][84]. Increasing physical activity through specific exercise training may therefore be an effective strategy for enhancing bone health.…”
Section: Exercise To Improve and Maintain Bone Health Poststrokementioning
confidence: 99%
“…Studies have shown that drinking milk can reduce bone loss. Because of estrogen, postmenopausal women are easy to bone loss, therefore, it's very important for postmenopausal women to drink milk [7].…”
Section: Editorialmentioning
confidence: 99%